Understanding better how emergency doctors work. Analysis of distribution of time and activities of emergency doctors: a systematic review and critical appraisal of time and motion studies. Issue 11 (5th September 2018) - Abdulwahid, Maysam Ali; Booth, Andrew; Turner, Janette; Mason, Suzanne M
Abstract : Background: Optimising the efficiency and productivity of senior doctors is critical to ED function and delivery of safe patient care. Time and motion studies (TMS) can allow quantification of how these doctors spend their working time, identify inefficiencies in the current work processes and provide insights into improving working conditions, and enhancing productivity. Three questions were addressed: (1) How do senior emergency doctors spend their time in the ED? (2) How much of their time is spent on multitasking? (3) What is the number of tasks completed per hour? Methods: The literature was systematically searched for TMS of senior emergency doctors. We searched for articles published in peer-reviewed journals in English language from 1998 to 2018 in the following databases: MEDLINE, EMBASE, Scopus, Web of Science and Cochrane. Studies were assessed for methodological quality using evidence-based quality criteria relevant for TMS including duration of observation, observer bias, Hawthorne effect and whether the task classification acknowledged any previous existing schemes. A narrative synthesis approach was followed. Results: Fourteen TMS were included. The studies were liable to several biases including observer and Hawthorne bias. Overall, the time spent on direct face-to-face contact with the patient accounted for at least around 25%–40% of the senior doctors' time. The remaining time was mostly spent on indirect clinical care such as communication (8%–44%), documentation (10%–28%) and administrative tasks (2%–20%). The proportion of time spent on multitasking ranged from 10% to 23%. When reported, the number of tasks performed per hour was generally high. Conclusion: The review revealed that senior doctors spent a large percentage of their time on direct face-to-face contact with patients. The review findings provided a grounded understanding of how senior doctors spent their time in the ED and could be useful in implementing improvements to the emergency care system.